Aplikasi Simponie sebagai Inovasi Pelayanan Publik untuk Meningkatkan Kualitas Pelayanan Perizinan di Kota Tangerang Selatan - Shofie Putri Fajrianti (Epistemik: Indonesian Journal of Social and Political Science, 2021)
This paper explains SIMPONIE Application as Public Service Innovation to Improve Quality in Licensing Services in South Tangerang City. This paper also further discusses One-stop integrated service organized by DPMPTSP based on the Simponie application. The purpose of this research is to know the innovations that made the south Tangerang City Government in an effort to improve the quality of licensing and the role of DPMPTSP in conducting public service innovations on the Simponie Application in an effort to improve the quality of licensing services. The theory used in this research is Rogers theory of innovation attribute theory. This theory uses five assessment indicators namely Relative Advantage, Compability, Complexity, Triability and Observability.. The research method used is descriptive qualitative research method. The results of this study indicate that the Simponie application-based service innovation is in accordance with the innovation attributes in improving licensing services in South Tangerang City but has not been carried out optimally.